High-strength composite board cast ingot blank for battery liquid cooling plate and preparation method of high-strength composite board cast ingot blank

In the casting process of Al-Mg-Si-Cu alloy, the preparation method of high-strength composite plate ingot blank is adopted, and the Zr, Ti and Be elements are reasonably added, and the casting conditions are controlled, which solves the problem of cracks and slag inclusions in the casting process, and significantly improves the yield and alloy performance.

CN119736527AActive Publication Date: 2025-04-01NORTHEAST LIGHT ALLOY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411939310.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Al-Mg-Si-Cu alloy is prone to cracks and slag inclusions during casting, resulting in low yield.

Method used

The preparation method of high-strength composite plate ingot blank for liquid-cooled battery plates is adopted. Through the steps of fine ingredients, smelting, casting and homogenizing annealing, Zr, Ti and Be elements are reasonably added to form stable compounds to improve the strength and corrosion resistance of the alloy, and to reduce slag inclusions and cracks by precisely controlling the casting conditions.

Benefits of technology

The yield rate of Al-Mg-Si-Cu alloy was significantly improved to 83%, and the strength and corrosion resistance of the alloy were improved, reducing cracks and slag inclusion defects during casting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736527A_ABST
    Figure CN119736527A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength composite plate cast ingot blank for a battery liquid cooling plate and a preparation method of the high-strength composite plate cast ingot blank, relates to an aluminum alloy cast ingot material and a manufacturing method of the aluminum alloy cast ingot material, and aims to solve the problem of low product rate of an aluminum alloy flat cast ingot manufactured by an existing method due to difficult casting forming and high possibility of slag inclusion in a steady casting state. The high-strength composite board cast ingot blank for the battery liquid cooling plate is prepared from Si, Cu, Mn, Mg, Zn, Ti, Zr, Be, Fe and Al. The method comprises the following steps: S1, weighing smelting raw materials; s2, smelting the smelting raw materials in sequence; and S3, casting the alloy melt to obtain the aluminum alloy flat cast ingot. According to the invention, the existing casting process is improved, and the crack defect of the cast ingot is reduced by combining the scientific proportion of the components and the fine operation in the production process, so that the yield of the cast ingot reaches 83%. The method is applied to the field of preparation of the ingot for the battery liquid cooling plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength composite plate ingot blank for a battery liquid cooling plate and a preparation method thereof. Background Art

[0002] Al-Mg-Si-Cu alloys have the advantages of good machinability, high strength, good surface treatment performance and good corrosion resistance. However, due to the complex chemical composition and phase composition, the alloy shows a great tendency to crack during casting, and the casting process parameter range is extremely narrow. Cracked waste often appears during the casting process. At the same time, there is a strong tendency to slag inclusion during the casting process, and slag inclusion cracks are prone to occur. The ingot yield rate is only 45%. Summary of the invention

[0003] The purpose of the present invention is to solve the problem of low yield of Al-Mg-Si-Cu alloy due to the difficulty in casting and easy slag inclusion in the steady state of casting, and to provide a high-strength composite plate ingot blank for battery liquid cooling plate and a preparation method thereof.

[0004] The high-strength composite plate ingot for a battery liquid cooling plate of the present invention is composed of 0.3-0.5% Si, 0.1-0.3% Cu, 0.05-0.15% Mn, 0.6-0.8% Mg, 0.1-0.3% Zn, 0.01-0.04% Ti, 0.03-0.06% Zr, 0.0001-0.0004% Be, Fe<0.15% and the balance Al, wherein the single impurity is ≤0.05% and the total impurity is ≤0.15%.

[0005] The present invention provides a method for preparing a high-strength composite plate ingot blank for a battery liquid cooling plate, which is carried out according to the following steps:

[0006] 1. Ingredients:

[0007] According to the mass fractions: Si is 0.3-0.5%, Cu is 0.1-0.3%, Mn is 0.05-0.15%, Mg is 0.6-0.8%, Zn is 0.1-0.3%, Ti is 0.01-0.04%, Zr is 0.03-0.06%, Be is 0.0001-0.0004%, Fe is less than 0.15% and the balance is Al, respectively weigh pure aluminum ingots, aluminum silicon master alloys, aluminum copper master alloys, aluminum manganese master alloys, pure magnesium ingots, pure zinc ingots, aluminum titanium master alloys, aluminum zirconium master alloys and aluminum beryllium master alloys;

[0008] 2. Melting:

[0009] The weighed pure aluminum ingot, aluminum silicon master alloy, aluminum copper master alloy, aluminum manganese master alloy and aluminum zirconium master alloy are added into a smelting furnace, and the pure zinc ingot is added after the melt softens and collapses. When the melt temperature reaches 720-730°C, the pure magnesium ingot, aluminum titanium master alloy and aluminum beryllium master alloy are added, and the mixture is stirred for 30-40 minutes by electromagnetic stirring at 720-760°C, and the chemical composition is analyzed by sampling. After the chemical composition is qualified, the mixture is covered with flux, and then introduced into a holding furnace at 720-760°C, and the mixture is refined for 30-40 minutes and then allowed to stand for 30-60 minutes to obtain a refined alloy melt.

[0010] 3. Casting:

[0011] At a temperature of 740℃~750℃, the refined alloy melt first flows into the online degassing device, then flows into the filtering device, and then passes through the flow plate at a casting speed of 38-40mm / min, a flow plate gate temperature of 695-705℃, and a casting cooling water flow rate of 95-105m 3 / h, under the condition of online seeding of Al-5Ti-B wire at 600-700 mm / min, the melt is injected into the crystallizer for semi-continuous casting to obtain an aluminum alloy ingot;

[0012] 4. Homogenization annealing:

[0013] The aluminum alloy ingot is heated to 545-555° C. and kept at 545-555° C. for 10-11 hours to obtain a high-strength composite plate ingot blank for a battery liquid cooling plate.

[0014] Beneficial effects of the present invention:

[0015] The high-strength composite plate ingot for high-performance Al-Mg-Si-Cu alloy battery liquid cooling plate prepared by the present invention has reasonably added Zr and Ti elements compared with the traditional Al-Mg-Si-Cu alloy. Zr and Al form ZrAl3 compounds, which play the role of hindering the recrystallization process, refining recrystallized grains and strengthening solid solution. Ti and Al form TiAl3 phases, which become non-spontaneous cores during crystallization, and can play the role of refining the cast structure. When Zr and Mn exist together, the impact strength of the alloy can also be significantly improved.

[0016] Be has active chemical properties and is an oxygen-philic element. It can form a dense oxide film on the metal surface and is stable even in the red-hot state in the air. It can improve the properties of the aluminum alloy oxide film, avoid oxidation slag inclusions in the casting process, and prevent slag inclusion cracks in the ingot.

[0017] Cu contributes to the material's high strength levels and enhances the material's overall wear resistance over time.

[0018] At the same time, the content of Fe impurities is strictly controlled when using refined aluminum ingots, and the impurity content is controlled at Fe < 0.15%. The main reason is that the Fe element can form a hard, brittle and insoluble compound FeSiAl5 (or Fe2Si2Al9), which reduces the plasticity of the alloy and is extremely easy to break during later rolling.

[0019] The high-strength composite plate ingot blank for the battery liquid cooling plate obtained by the present invention has qualified chemical composition, no defects such as cracks and slag inclusions on the surface, and the yield rate reaches 83%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a physical picture of the high-strength composite plate ingot blank for the battery liquid cooling plate prepared in the example. DETAILED DESCRIPTION

[0021] Specific implementation method 1: In this implementation method, a high-strength composite plate ingot for a battery liquid cooling plate is composed of 0.3-0.5% Si, 0.1-0.3% Cu, 0.05-0.15% Mn, 0.6-0.8% Mg, 0.1-0.3% Zn, 0.01-0.04% Ti, 0.03-0.06% Zr, 0.0001-0.0004% Be, Fe<0.15% and the balance Al, wherein a single impurity is ≤0.05% and a total impurity is ≤0.15%.

[0022] The aluminum content of the pure aluminum ingot described in this embodiment is 99.85%. The silicon content in the aluminum-silicon master alloy is 20%, the copper content in the aluminum-copper master alloy is 40%, the manganese content in the aluminum-manganese master alloy is 10%, the titanium content in the aluminum-titanium master alloy is 6%, the zirconium content in the aluminum-zirconium master alloy is 3%, and the beryllium content in the aluminum-beryllium master alloy is 3%.

[0023] Specific implementation method 2: In this implementation method, a method for preparing a high-strength composite plate ingot blank for a battery liquid cooling plate is carried out according to the following steps:

[0024] 1. Ingredients:

[0025] According to the mass fractions: Si is 0.3-0.5%, Cu is 0.1-0.3%, Mn is 0.05-0.15%, Mg is 0.6-0.8%, Zn is 0.1-0.3%, Ti is 0.01-0.04%, Zr is 0.03-0.06%, Be is 0.0001-0.0004%, Fe is less than 0.15% and the balance is Al, respectively weigh pure aluminum ingots, aluminum silicon master alloys, aluminum copper master alloys, aluminum manganese master alloys, pure magnesium ingots, pure zinc ingots, aluminum titanium master alloys, aluminum zirconium master alloys and aluminum beryllium master alloys;

[0026] 2. Melting:

[0027] The weighed pure aluminum ingot, aluminum silicon master alloy, aluminum copper master alloy, aluminum manganese master alloy and aluminum zirconium master alloy are added into a smelting furnace, and the pure zinc ingot is added after the melt softens and collapses. When the melt temperature reaches 720-730°C, the pure magnesium ingot, aluminum titanium master alloy and aluminum beryllium master alloy are added, and the mixture is stirred for 30-40 minutes by electromagnetic stirring at 720-760°C, and the chemical composition is analyzed by sampling. After the chemical composition is qualified, the mixture is covered with flux, and then introduced into a holding furnace at 720-760°C, and the mixture is refined for 30-40 minutes and then allowed to stand for 30-60 minutes to obtain a refined alloy melt.

[0028] 3. Casting:

[0029] At a temperature of 740℃~750℃, the refined alloy melt first flows into the online degassing device, then flows into the filtering device, and then passes through the flow plate at a casting speed of 38-40mm / min, a flow plate gate temperature of 695-705℃, and a casting cooling water flow rate of 95-105m 3 / h, under the condition of online seeding of Al-5Ti-B wire at 600-700 mm / min, the melt is injected into the crystallizer for semi-continuous casting to obtain an aluminum alloy ingot;

[0030] 4. Homogenization annealing:

[0031] The aluminum alloy ingot is heated to 545-555° C. and kept at 545-555° C. for 10-11 hours to obtain a high-strength composite plate ingot blank for a battery liquid cooling plate.

[0032] Specific embodiment 3: This embodiment differs from specific embodiment 2 in that the flux covered in step 2 is composed of 40% KCl, 45% MgCl2, 8% BaCl2, and 7% NaCl+CaCl2 by mass percentage, and the added amount is 5 kg / ton of melt. Others are the same as specific embodiment 2.

[0033] Specific embodiment 4: This embodiment differs from specific embodiment 2 or 3 in that: in step 2, the electromagnetic stirring frequency is 0.8 Hz, the intensity is set to 80%, the reversal time is 180 s, the reversal interval time is 15 s, and the stirring time is 30 min. Others are the same as specific embodiment 2 or 3.

[0034] Specific embodiment 5: This embodiment differs from specific embodiments 2 to 4 in that the refining gas in step 2 is 99.99% argon, the flow rate is set to 20Nl / min, and the operation time is set to 30min. The rest is the same as specific embodiments 2 to 4.

[0035] Specific embodiment 6: This embodiment is different from specific embodiments 2 to 5 in that the purity of the gas in the degassing device in step 3 is 99.99% argon. The rest is the same as specific embodiments 2 to 5.

[0036] Specific embodiment 7: This embodiment is different from specific embodiments 2 to 6 in that the filtering device in step 3 adopts double-stage filtering, and the precision of the ceramic sheets is 30 mesh and 50 mesh respectively. The rest is the same as specific embodiments 2 to 6.

[0037] Specific embodiment eight: This embodiment differs from any one of specific embodiments two to seven in that: in step three, the material temperature of the insulation furnace is 740°C, the casting speed is 40 mm / min, the flow plate gate temperature is 695°C, and the casting cooling water flow rate is 100 m 3 / h under the condition of semi-continuous casting. The rest is the same as one of the second to seventh embodiments.

[0038] Specific embodiment 9: This embodiment differs from specific embodiments 2 to 8 in that: in step 3, the Ti content of the online sowing Al-5Ti-B wire is 5%, the B content is 1%, and the rest is Al, and the sowing speed is 680 mm / min. The rest is the same as specific embodiments 2 to 8.

[0039] Specific embodiment 10: This embodiment differs from specific embodiments 2 to 9 in that: in step 4, the homogenization annealing is performed at a temperature of 550° C. for 10 hours. The rest is the same as specific embodiments 2 to 9.

[0040] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0041] The present application is described in detail below with reference to specific embodiments:

[0042] Example 1: A high-strength composite plate ingot for a battery liquid cooling plate and a preparation method thereof, which is carried out according to the following steps:

[0043] Step S1: Ingredients:

[0044] According to the mass fractions: Si is 0.42%, Cu is 0.25%, Mn is 0.12%, Mg is 0.75%, Zn is 0.25%, Ti is 0.025%, Zr is 0.05%, Be is 0.0003%, Fe is less than 0.15%, and the balance is Al, respectively weigh pure aluminum ingots with an aluminum content of 99.85%, aluminum-silicon master alloys, aluminum-copper master alloys, aluminum-manganese master alloys, pure magnesium ingots, pure zinc ingots, aluminum-titanium master alloys, aluminum-zirconium master alloys, and aluminum-beryllium master alloys;

[0045] Step S2: Smelting:

[0046] First, the pure aluminum ingot, aluminum-silicon master alloy, aluminum-copper master alloy, aluminum-manganese master alloy and aluminum-zirconium master alloy weighed in step S1 are added to a smelting furnace, and a pure zinc ingot is added after the melt softens and collapses. When the melt temperature reaches 725°C, a magnesium ingot, an aluminum-titanium master alloy and an aluminum-beryllium master alloy are added, and the mixture is stirred for 40 minutes at 730°C by electromagnetic stirring, and the chemical composition is analyzed by sampling. After the chemical composition is qualified, the mixture is covered with a flux, and the melt is introduced into a holding furnace at 740°C, and the air-permeable brick is opened for refining for 30 minutes, and then the mixture is allowed to stand for 50 minutes to obtain a refined alloy melt;

[0047] Step S3: Casting:

[0048] At a temperature of 740°C, the refined alloy melt obtained in the holding furnace first flows into the online degassing device, then into the filtration device, and then passes through the flow plate at a casting speed of 38mm / min, a flow plate gate temperature of 698°C, and a casting cooling water flow rate of 95m 3 / h, under the condition of online seeding of Al-5Ti-B wire at 680 mm / min, the melt was injected into the crystallizer for semi-continuous casting to obtain an aluminum alloy ingot with a size of 440 mm×1450 mm×4320 mm;

[0049] Step S4: Homogenization annealing:

[0050] The aluminum alloy ingot obtained in step S3 is heated to 550° C. and kept at 550° C. for 10 hours to obtain a high-strength composite plate ingot blank for a battery liquid cooling plate.

[0051] The chemical composition of the high-strength composite plate ingot for the battery liquid cooling plate obtained in this embodiment is qualified, there are no defects such as cracks and slag inclusions on the surface, and the yield rate reaches 83%.

Claims

1. A high-strength composite plate ingot for a battery liquid cooling plate, characterized in that: The ingot blank is composed of 0.3-0.5% Si, 0.1-0.3% Cu, 0.05-0.15% Mn, 0.6-0.8% Mg, 0.1-0.3% Zn, 0.01-0.04% Ti, 0.03-0.06% Zr, 0.0001-0.0004% Be, Fe<0.15% and the balance Al by mass fraction.

2. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 1, characterized in that: The method proceeds as follows:

1. Ingredients: According to the mass fractions: Si is 0.3-0.5%, Cu is 0.1-0.3%, Mn is 0.05-0.15%, Mg is 0.6-0.8%, Zn is 0.1-0.3%, Ti is 0.01-0.04%, Zr is 0.03-0.06%, Be is 0.0001-0.0004%, Fe is less than 0.15% and the balance is Al, respectively weigh pure aluminum ingots, aluminum silicon master alloys, aluminum copper master alloys, aluminum manganese master alloys, pure magnesium ingots, pure zinc ingots, aluminum titanium master alloys, aluminum zirconium master alloys and aluminum beryllium master alloys; 2. Melting: The weighed pure aluminum ingot, aluminum silicon master alloy, aluminum copper master alloy, aluminum manganese master alloy and aluminum zirconium master alloy are added into a smelting furnace, and the pure zinc ingot is added after the melt softens and collapses. When the melt temperature reaches 720-730°C, the pure magnesium ingot, aluminum titanium master alloy and aluminum beryllium master alloy are added, and the mixture is stirred for 30-40 minutes by electromagnetic stirring at 720-760°C, and the chemical composition is analyzed by sampling. After the chemical composition is qualified, the mixture is covered with flux, and then introduced into a holding furnace at 720-760°C, and the mixture is refined for 30-40 minutes and then allowed to stand for 30-60 minutes to obtain a refined alloy melt.

3. Casting: At a temperature of 740℃~750℃, the refined alloy melt first flows into the online degassing device, then flows into the filtering device, and then passes through the flow plate at a casting speed of 38-40mm / min, a flow plate gate temperature of 695-705℃, and a casting cooling water flow rate of 95-105m 3 / h, under the condition of online seeding of Al-5Ti-B wire at 600-700 mm / min, the melt is injected into the crystallizer for semi-continuous casting to obtain an aluminum alloy ingot; 4. Homogenization annealing: The aluminum alloy ingot is heated to 545-555° C. and kept at 545-555° C. for 10-11 hours to obtain a high-strength composite plate ingot blank for a battery liquid cooling plate.

3. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: The flux covered in step 2 is composed of 40% KCl, 45% MgCl2, 8% BaCl2, and 7% NaCl+CaCl2 in mass percentage, and the added amount is 5 kg / ton of melt.

4. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: In step 2, the electromagnetic stirring frequency is 0.8 Hz, the intensity is set to 80%, the reversal time is 180 s, the reversal interval time is 15 s, and the stirring time is 30 min.

5. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: In step 2, the refining gas is 99.99% argon, the flow rate is set to 20 Nl / min, and the operation time is set to 30 min.

6. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: The gas purity in the degassing device in step 3 is 99.99% argon.

7. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: In step three, the filtering device adopts double-stage filtering, and the precision of the ceramic sheets is 30 mesh and 50 mesh respectively.

8. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: Step 3: Keep the furnace temperature at 740℃, casting speed at 40mm / min, flow plate gate temperature at 695℃, casting cooling water flow at 100m 3 Semi-continuous casting is carried out under the condition of / h.

9. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: Step 3: Online seeding of Al-5Ti-B wire with a Ti content of 5%, a B content of 1% and the remainder of Al, and a seeding speed of 680 mm / min.

10. The method for preparing a high-strength composite plate ingot for a battery liquid cooling plate according to claim 2, characterized in that: In step 4, the homogenization annealing is carried out at a temperature of 550° C. for 10 hours.

Citation Information

Patent Citations

  • Aluminum alloy round cast ingot for high-quality welding wires and manufacturing method thereof

    CN103469036A

  • Large-size high-magnesium rare earth aluminum alloy cast ingot and manufacturing method thereof

    CN110724863A

  • High-strength low-quenching-sensitivity aluminum alloy and preparation method of aluminum alloy and aluminum alloy profile

    CN115466888A

  • Al-Mg-Mn-Zn-Zr welding wire alloy cast ingot for high-strength fusion welding and preparation method thereof

    CN116000498A

  • Al ALLOY CASTING AND PRODUCTION METHOD THEREOF

    JP2018024922A